A Shoreline Change Detection (2012-2021) and forecasting Using Digital Shoreline Analysis System (DSAS) Tool: A Case Study of Dahej Coast, Gulf of Khambhat, Gujarat, India - Mousumi Dey; Shanmuga Priyaa S; B. K. Jena (Faculty of Geography, Universitas Gadjah Mada, 2021)
Shoreline is one of the coastal landforms which continuously changing in nature. Hence, monitoring of shoreline change is very obligate to understand and manage the coastal process. The objectives of the present study were i) to identify the shoreline change detection (2012 to 2021) based on various statistical methods along Dahej coast, Gujrat. ii) to forecast the shoreline position after 10 years. DSAS tool and Multi-dated satellite images (Sentinel-2 and LISS-IV) were used in present study. The result shows that, the pattern of rate of change was more or less similar with little variation in the values for the 3 different methods. Highest erosion rate was for End Point Rate, Linear Regression Rate and Weighted Linear Regression rate found -33m, -31m, -31m respectively at transect no 54. Highest accretion rate was 38m (EPR), 50m (LRR), 51m (WLR) along a particular transect. The forecast of shoreline position for the year 2032 observed through Kalman Filter Model. Seasonal analysis for 3 years (2016, 2017, 2018) shows the region not having any seasonal pattern.